2000
DOI: 10.1021/jf000285z
|View full text |Cite
|
Sign up to set email alerts
|

Observations on Metal Concentrations in Three Species of Shark (Deania calcea, Centroscymnus crepidater, and Centroscymnus owstoni) from Southeastern Australian Waters

Abstract: Deep sea dog sharks (Deania calcea, Centroscymnus crepidater, and Centroscymnus owstonii) were captured from the waters off western Victoria, Australia, in April and May 1998. The elements As, Ca, Cd, Cu, Fe, Hg, K, Mg, Mn, Na, Sr, and Zn were detected in the muscle tissue. The concentrations of Al, Ba, Be, Cr, Mo, Ni, Pb, and V were below the detection limits of the instrumental techniques employed (ICP-ES and GF-AAS). However, significant concentration differences between species were detected for As, Cd, Hg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 26 publications
4
31
1
Order By: Relevance
“…This pattern has been extensively exhibited in previous studies of sharks (Forrester et al, 1972;Walker, 1976Walker, , 1988Taguchi et al, 1979;Hueter et al, 1995). For C. crepidater analysed in this study, comparable Hg levels and a similar relationship between size and Hg levels was observed by Davenport (1995) and Turoczy et al, (2000). The accumulation of mercury with increasing size (fundamentally age) is likely to also reflect other ecological and physical factors, such as differential feeding ecology, and slow and inefficient elimination of mercury from deeper dwelling species (Trudel and Rasmussen, 1997).…”
Section: Mercury and Shark Life-cyclesupporting
confidence: 88%
See 2 more Smart Citations
“…This pattern has been extensively exhibited in previous studies of sharks (Forrester et al, 1972;Walker, 1976Walker, , 1988Taguchi et al, 1979;Hueter et al, 1995). For C. crepidater analysed in this study, comparable Hg levels and a similar relationship between size and Hg levels was observed by Davenport (1995) and Turoczy et al, (2000). The accumulation of mercury with increasing size (fundamentally age) is likely to also reflect other ecological and physical factors, such as differential feeding ecology, and slow and inefficient elimination of mercury from deeper dwelling species (Trudel and Rasmussen, 1997).…”
Section: Mercury and Shark Life-cyclesupporting
confidence: 88%
“…Results of several studies around southeastern Australia (Walker, 1988;Davenport, 1995;Turoczy et al, 2000) show similar mean mercury levels in the muscle tissue to those reported in this study. Comparable elevated levels are also documented in several demersal sharks, globally (De Pinho et al, 2002;.…”
Section: Interspecific Local and Regional Hg Variations In Sharks Musupporting
confidence: 86%
See 1 more Smart Citation
“…This finding is well illustrated by the strong associations between body length and muscle Hg concentrations that have been observed for several shark species (Turoczy et al 2000;Gelsleichter and Walker 2010;Storelli et al 2011;Hurtado-Banda et al 2012;Maz-Courrau et al 2012;Delshad et al 2012). In the current study, although all scalloped hammerhead sharks were juvenile with relatively low variation in body size, significant correlations were found between total length and weight and Hg concentration in muscle and liver, but it was found that Hg in muscle increased and Hg in liver decreased as total length and weight incremented.…”
Section: Discussionmentioning
confidence: 58%
“…Squalene has a chemopreventive effect on colon cancer (14). Moreover, squalene has wide applications in fine chemicals, magnetic tape, and low-temperature lubricants and as an additive in animal feed (1).The use of shark liver oil is limited, due to the presence of environmental pollutants, such as polychlorinated biphenyls, heavy metals, and methylmercury residues, as well as an unpleasant fishy odor and taste (17,19). Moreover, the presence of similar compounds, such as cholesterol, in the oils from marine animal liver can make squalene purification difficult.…”
mentioning
confidence: 99%